Implementação de código computacional para análise estática de treliças planas via método dos elementos finitos - Souza, Diego Aparecido de (2022)
Truss is one of the most used structural systems in Engineering. Solving for the axial forces due to the actions applied to a truss can be done by classical analytical processes, such as the force method and the displacement method. However, depending on the number of elements and their degree of hyperstaticity, these manual processes can last for hours. Thus, it is of fundamental importance that the engineering professional has a computational tool, as a way to reduce time and errors in the structural analysis. The objective of the present work was to implement a computer program for solving plane trusses using the Finite Element Method. The program was written in Scilab language considering the context of linear elastic material and small displacement theory. Four examples were solved with the code developed and the results were compared with the solutions obtained with the Ftool and Risa 2D softwares. The results obtained by the developed computer code were considered valid, since the numerical from the results were less than 0,2% in all cases.